Estudo sobre a situação da logística reversa de lâmpadas fluorescentes conforme estabelecido pelo Plano Nacional de Resíduos Sólidos no Brasil - Domingues, Estefani Aparecida (Universidade Federal de São Carlos, 2023)
In modern times, electricity has become a vital necessity, but its use can trigger a series of problems related to improper waste disposal, often resulting in the release of harmful substances into the environment and human health. These substances include elements such as mercury and lead, which can cause neurological damage, kidney and respiratory problems. In addition, this type of improper disposal can cause serious environmental damage, polluting the soil, water, and air. In this context, the importance of implementing public policies and environmental awareness focused on proper disposal stands out. This study aimed to investigate the problems arising from improper disposal of such waste and to assess the level of understanding of the target audience regarding the concept of reverse logistics, through the application of a form. The analysis of the responses revealed a lack of overall understanding of the concept of reverse logistics and also regarding the proper disposal of fluorescent lamps by a large part of those surveyed. Thus, a proposed solution would be the implementation of environmental education programs, combined with investments in public policies, aiming to raise awareness among the population about the importance of environmentally sound disposal and to encourage them to adopt the practice of reverse logistics in a safe manner. Additionally, this study sought to elucidate the harms resulting from improper disposal and the benefits arising from reverse logistics regulated by Decree No. 10,936/2022. Keywords: Fluorescent lamps. Reverse logistics. National Solid Waste Plan.
Study on the reverse logistic situation of fluorescents lamps as established by Solid Waste National Plan in Brazil
Keywords: Lâmpadas fluorescentes; Logística reversa; Plano Nacional de Resíduos Sólidos; Fluorescent lamps; Reverse logistic; National Solid Waste Plan; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO